Produção de haloalcaloides por fungos de ambiente terrestre - Silva, José Vinicius da (Universidade Federal de São Carlos, 2016)
The production of secondary metabolites by microorganisms is a tool to find new substances with potential pharmacological activities of human interest. Thus, the search for more extreme environments or even exposure of isolated in extreme conditions lead to the production of new natural products. The fungus Penicillium chrysogenum was able to produce the containing bromine atom alkaloid derived from the biosynthetic pathway of dicetopiperazinic alkaloids. Under natural conditions, the fungus produces roquefortine C, when the culture medium was added ammonium bromide, the microorganism produced 11-bromoroquefortine D, 11-bromoroquertine C and 17-oxy-11-C bromoroquefortine. These metabolites have biosynthetic origin by condensation of tryptophan with histidine and trimethyalil group. There are reports in the literature that the first biosynthetic step of halogenated alkaloid derivatives of tryptophan would be halogenation of this amino acid. The synthesis of bromotryptophan was performed and the formation of three regioisomers were detected. The extract containing the isomers was added to the culture medium during the growth of the fungus and analysis of LCHRMS/MS observed the formation of 11-bromoroquefortine C. Synthesis of roquefortine C with sodium hypobromite has also led to the formation of 11-bromoroquefortine C. During the search of the gene responsible for the expression of halogenase in Penicillium chrysogenum a gene fragment compatible with halogenases deposited in databases was detected and isolated. In Talaromyces wortmannii, fungus isolated from Mallus domestica, producer of some halogenated alkaloid known as rugulovasins, a gene fragment compatible with fungal halogenases was also detected and isolated. Strains belonging to Penicillium and Aspergillus isolated and deposited in mycology collection of LaBioMMi were grown on solid medium and analyzed by MALDI-TOF to build a database. All the microorganisms were separated by gender and grouped into dendrograms for checking the similarity between species. It was also found that the modification of the culture medium does not influence directly the profile obtained from microorganisms.
Haloalkaloids production by terrestrial fungi
Keywords: Talaromyces wortmannii; Bromoroquefortina; Haloalcaloides; Microrganismos endofíticos; Osmac; Penicillium chrysogenum; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS